Leadership - What Really Matters A Handbook on Systemic Leadership - Pinnow, Daniel F.; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
What is really important in day to day leadership?  How is a good and effective manager characterized? Daniel F. Pinnow describes the essentials of collaboration in the business environment in a very illustrative way. This standard reference book exists as a 5th edition in German and is also available in Chinese. It provides a comprehensive and easy-to-understand overview over the most important leadership approaches in theory and practice. The credo of the author is: Leadership is an art of creating a world where others would love to join in.
Electronic reproduction.
Keywords: Leadership; LeadershipSvHandbooks, manuals, etc; Electronic books